The relationship between attitude and self-efficacy of labor support with supportive behaviors from the perspective of midwives - Khadijeh Heidari; Leila Amiri-Farahani; Sally Pezaro (BMC, 2023)
Abstract Background and aim Effective support given by a midwife during labor and childbirth is associated with numerous positive outcomes. Yet the delivery of such support can be hindered by negative workplace cultures. The purpose of the current study was to examine the relationship between attitude and self-efficacy of labor support and labor supportive behaviors from the perspectives of midwives working in Iran. Methods Midwives (n = 213) employed in the labor wards of selected hospitals in an urban area of Iran participated in this cross-sectional study. Participants were recruited via convenience sampling from December 2016 to September 2017. The data were collected using a personal characteristics tool, the Labor Support Questionnaire, the Self-efficacy Labor Support Scale, and attitudes toward the Labor Support Questionnaire. Descriptive statistics along with multiple linear regression was used for data analysis. Results Participants had a supportive behavior score of 74.98 for mean (SD ± 13.39). The informational support dimension had the highest reported score of the supportive behaviors, whereas the tangible support dimension had the lowest score. The mean scores of attitude and self-efficacy toward labor support were 24.79 (SD ± 4.14) and 79.83 (SD ± 13.82). There were also statistically significant correlations between attitude and self-efficacy, and labor support behaviors and its dimensions. Multiple linear regression analysis results indicated that interests in occupation, attitude, and self-efficacy were predictors of labor supportive behaviors. Conclusion Midwives' level of interest in the profession, attitude, and self-efficacy of labor support were significantly associated with labor support behaviors. Thus midwives' interest in their profession, along with their attitudes and self-efficacy could usefully be developed to enhance their supportive behaviors during labor.